2008
DOI: 10.1073/pnas.0810108105
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid male sterility in rice controlled by interaction between divergent alleles of two adjacent genes

Abstract: Sterility is common in hybrids between divergent populations, such as the indica and japonica subspecies of Asian cultivated rice (Oryza sativa). Although multiple loci for plant hybrid sterility have been identified, it remains unknown how alleles of the loci interact at the molecular level. Here we show that a locus for indicajaponica hybrid male sterility, Sa, comprises two adjacent genes, SaM and SaF, encoding a small ubiquitin-like modifier E3 ligase-like protein and an F-box protein, respectively. Most i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
257
3
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 238 publications
(272 citation statements)
references
References 32 publications
8
257
3
1
Order By: Relevance
“…At the hybrid male sterility locus Sa, heterozygotes of Indica allele Sa i and Japonica allele Sa j exhibited male semisterility. Long et al (2008) In this study, the physical distance between the KGC11M1 and RM27122 markers was found to be 1,637 kb. According to the Rice Genome Annotation Project (Ouyang et al 2007, http://rice.plantbiology.msu.…”
Section: T14×(t65×ptb7)]mentioning
confidence: 54%
See 1 more Smart Citation
“…At the hybrid male sterility locus Sa, heterozygotes of Indica allele Sa i and Japonica allele Sa j exhibited male semisterility. Long et al (2008) In this study, the physical distance between the KGC11M1 and RM27122 markers was found to be 1,637 kb. According to the Rice Genome Annotation Project (Ouyang et al 2007, http://rice.plantbiology.msu.…”
Section: T14×(t65×ptb7)]mentioning
confidence: 54%
“…Many postzygotic reproductive barrier forms have been reported in rice (Oryza sativa), such as hybrid weakness (e.g., Oka 1957), hybrid pollen sterility (e.g., Long et al 2008), and hybrid sterility causing female gamete abortion (e.g., Chen et al 2008). Among them, hybrid weakness is definable as weak growth occurring in F 1 hybrids derived from crosses between two normal strains.…”
Section: Introductionmentioning
confidence: 99%
“…Despite this progress, several factors motivate additional genetic studies of postzygotic isolation. Although other species have provided important insights (e.g., Sweigart et al 2006;Bomblies et al 2007;Moyle 2007;Chen et al 2008;Lee et al 2008;Long et al 2008;Kao et al 2010;Martin and Willis 2010), current knowledge of the genetics of postzygotic isolation remains highly biased toward Drosophila. In addition, some of the best-studied species hybridize rarely or not at all in the wild, complicating attempts to connect reproductive barriers examined in the lab with gene flow in nature.…”
mentioning
confidence: 99%
“…TRD is induced by a variety of mechanisms, such as non-random chromosome segregation during meiosis (Birchler et al, 2003;Fishman and Saunders, 2008), preferential gamete dysfunction in hybrids (Lyttle, 1991;Moyle and Graham, 2006;Long et al, 2008;Chen et al, 2008;Tao et al, 2009a, b;Phadnis and Orr, 2009) and preferential gamete success during fertilization (Price, 1997;. Because TRD can dramatically alter the frequency of alleles in a population by disrupting proper Mendelian segregation, it has been hypothesized that TRD is a driving force in the emergence of a reproductive barrier (Frank, 1991;Hurst and Pomiankowski, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…Among them, TRD occurring in either the male (mTRD) or female (fTRD) gametes has been frequently reported and some of the genes causing sex-specific TRD have been cloned Long et al, 2008). On the other hand, there are few reports on sex-independent TRD (siTRD), which results from preferential transmission of both male and female gametes carrying one of the two alleles in the heterozygote (Rick, 1966;Koide et al, 2008c).…”
Section: Introductionmentioning
confidence: 99%